2015
DOI: 10.3340/jkns.2015.57.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Intramedullary Abscess Caused by a Missed Congenital Dermal Sinus

Abstract: Congenital dermal sinus (CDS) is a type of occult spinal dysraphism characterized by a midline skin dimple. A 12-month-old girl presented with fever and ascending quadriparesis. She had a midline skin dimple in the upper sacral area that had been discovered in her neonatal period. Imaging studies revealed a holocord intramedullary abscess and CDS. Overlooking CDS or misdiagnosing it as benign sacrococcygeal dimple may lead to catastrophic infection and cause serious neurological deficits. Therefore, further im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…In some cases reported in literature, full recovery has been reported, while in 20% there has not been full recovery [4]. It has been reported that neurological recovery could be related to the rate and level of intramedullary involvement and the time of diagnosis and surgery [2]. Delays in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases reported in literature, full recovery has been reported, while in 20% there has not been full recovery [4]. It has been reported that neurological recovery could be related to the rate and level of intramedullary involvement and the time of diagnosis and surgery [2]. Delays in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The complication of Several authors have recommended early surgery for these patients [1,2,4]. Drainage of the abscess with laminectomy and dorsal midline myelectomy is an effective method for the control of infection and functional recovery [2]. Laminectomy at multiple levels is not recommended as the risk of later stage complications is increased [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore whenever a dermal sinus is noted in a new born baby possibility of spinal dysraphism has to be ruled out and treated accordingly before it creates a catastrophic infection of the spinal cord. 4 CDS is the commonest cause of intramedullary spinal cord abscess. 5 Hear we present an infant with intramedullary abscess presented with paraparesis and bowel and bladder involvement.…”
mentioning
confidence: 99%